Decentralized internet infrastructure - Bingyang LIU; Fei YANG; Shoushou REN; Xinpeng WEI; Xue YANG; Chuang WANG; Zhiwei YAN (Dianxin kexue, 2019)
Inter-domain routing system,domain name system (DNS) and public key infrastructure (PKI) are the fundamental infrastructures of the internet.These infrastructures help to provide network connectivity,service availability and communication trusts between different internet entities.However,these infrastructures are all designed based on a centralized system architecture or a trusted model,which suffers from many vulnerabilities.An architecture called decentralized internet infrastructure (DII) based on decentralization techniques was proposed.The DII architecture consists of three layers.The underlying layer was the distributed ledger layer,providing decentralized trusted foundation for DII.The intermediate layer,called name space management layer,fulfills the management of internet core resources (such as IP addresses,AS numbers and domain names) and provides trustworthy mapping information between different resources.The top layer was an open application layer that could support trustworthy decentralized internet applications.